As relações públicas no rádio: estudos dos instrumentos das relações públicas a partir da análise do quadro radiofônico projeto fitness da Fronteira FM – São Borja – RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This term paper is about how the concepts and instruments of Public Relations course are applied to this radio show called Projeto Fitness, on Radio Fronteira FM, which is in São Borja, RS, Brazil, as well as its stakeholders. You will find a brief history of PR from the moment it was created in the USA to the moment it was implemented in Brazil, we will look at its concepts, instruments and techniques so the actions to do with the course can be carried out. The stakeholders of radio fronteira fm will be also looked at. Split in 4 parts, the first one being about the concepts, instruments, and the public affairs. Then, the research carried out through “projeto fitness” that aired between january and april/2017, investigating what a public relations professional, does as well as the instruments and techniques taken into account and an analysis of the stakeholders involved. One of the 4 parts is about the repercussion of “projeto fitness” on social media sites and newspaper. Discussing the theme to help future researches is the aim of this paper. It is not intended to get results that will make us come to conclusions. Even thought there was no department or Public Relations professional around with the mastering of techniques, instruments and concepts of Public Relations, it was clear by the end of this paper what an Public Relations professional does.
Keywords: Relações Públicas; Rádio – Programas; Rádio Fronteira FM (São Borja, RS); Public Relations; CNPQ::CIENCIAS SOCIAIS APLICADAS